Cost and Toxicity Comparisons of Two IMRT Techniques for Prostate Cancer: A Micro-Costing Study and Weighted Propensity Score Analysis Based on a Prospective Study - Masson, Ingrid; Bellanger, Martine; Perrocheau, Geneviève; Mahé, Marc-André; Azria, David; Pommier, Pascal; Mesgouez-Nebout, Nathalie; Giraud, Philippe; Peiffert, Didier; Chauvet, Bruno; Dudouet, Philippe; Salem, Naji; et al. (Frontiers in Oncology, 2022)
Background: Intensity modulated radiation therapy (IMRT) combined with androgen deprivation therapy (ADT) has become the standard treatment for patients with high-risk prostate cancer. Two techniques of rotational IMRT are commonly used in this indication: Volumetric Modulated Arc Therapy (VMAT) and helical tomotherapy (HT). To the best of our knowledge, no study has compared their related costs and clinical effectiveness and/or toxicity in prostate cancer. We aimed to assess differences in costs and toxicity between VMAT and HT in patients with high-risk prostate cancer with pelvic irradiation. Material and methods: We used data from the “RCMI pelvis” prospective multicenter study (NCT01325961) including 155 patients. We used a micro-costing methodology to identify cost differences between VMAT and HT. To assess the effects of the two techniques on total actual costs per patient and on toxicity we used stabilized inverse probability of treatment weighting. Results: The mean total cost for HT, €2019 3,069 (95% CI, 2,885 - 3,285) was significantly higher than the mean cost for VMAT €2019 2,544 (95% CI, 2,443 – 2,651) (p <.0001). The mean ± SD labor and accelerator cost for HT was €2880 (±583) and €1978 (±475) for VMAT, with 81% and 76% for accelerator, respectively. Acute GI and GU toxicity were more frequent in VMAT than in HT (p=.021 and p=.042, respectively). Late toxicity no longer differed between the two groups up to 24 months after completion of treatment. Conclusion: Use of VMAT was associated with lower costs for IMRT planning and treatment than HT. Similar stabilized long-term toxicity was reported in both groups after higher acute GI and GU toxicity in VMAT. The estimates provided can benefit future modeling work like cost-effectiveness analysis.